2007
DOI: 10.1111/j.1740-8784.2007.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Intervening in Employee Disputes: How and When Will Managers from China, Japan and the USA Act Differently?

Abstract: We investigated how third party managers from China, Japan and the USA intervened in employees' disputes. Consistent with predictions, we found (using non‐linear HLM analysis) that managers who were superiors to the disputants behaved autocratically and/or decided on conservative (e.g., contract adhering) outcomes; but managers who were peers (especially in China and the USA), generally involved disputants in decision‐making and obtained integrative outcomes that went beyond initial contract related mandates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…People form expectations of others’ power and influence depending on the contexts in which their social interaction occurs (Bugental, Blue, & Cruzcosa, ). Prior research on third party managers also shows this effect (Brett et al., ; Karambayya & Brett, ; Karambayya et al., ).
H1: Disputants will report that male and female third party managers with role authority (the boss condition) were more likely to make the decision to resolve the dispute than male and female third parties in the peer condition.
…”
Section: Hypothesesmentioning
confidence: 77%
See 2 more Smart Citations
“…People form expectations of others’ power and influence depending on the contexts in which their social interaction occurs (Bugental, Blue, & Cruzcosa, ). Prior research on third party managers also shows this effect (Brett et al., ; Karambayya & Brett, ; Karambayya et al., ).
H1: Disputants will report that male and female third party managers with role authority (the boss condition) were more likely to make the decision to resolve the dispute than male and female third parties in the peer condition.
…”
Section: Hypothesesmentioning
confidence: 77%
“…This is a high standard for female third party managers to achieve. This is the outcome that prior research has shown, that third party managers with authority tend to impose on disputants, while third party managers without authority tend to facilitate a short‐term integration of disputants’ interests (Brett et al., ; Karambayya & Brett, ; Karambayya et al., ). Thus, we propose
H2: Female third parties without authority are more likely to facilitate an outcome that requires a disputant to concede on his or her interests but protects the reputation of the company than male third parties without authority or male or female third parties with authority to impose an outcome on the disputants.
…”
Section: Hypothesesmentioning
confidence: 78%
See 1 more Smart Citation
“…Greater sensitivity of Chinese organizational leaders to contextual aspects was also found in dispute-resolution situations. Brett, Tinsley, Shapiro, and Okumura (2007) showed that decision-related behaviours of Chinese managers were predicted by contextual cues in the environment. where standards still fail to match expected levels.…”
Section: Resultsmentioning
confidence: 99%
“…Building on the rich literature in anthropology and communication, Jeanne and her coauthors began to define and test negotiation norms in the United States (information exchange) and Japan (power and distributive tactics; Brett & Okumura, ) and conflict resolution norms in the United States (discussing interests and synthesizing issues) and Hong Kong (concern for the collective and concern for authority; Tinsley & Brett, ). More recent work examines both norm complexity and situational primes to explain cultural variation in how managers (vs. peers) utilize authoritative (vs. participative) mediation strategies in China, Japan, and the United States (Brett, Tinsley, Shapiro, & Okumura, ).…”
Section: Making Global Connections—wendi L Adairmentioning
confidence: 99%